Foreign investors' activities in Eastern Germany motivations and strategies - Birgit Sander (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
The paper analyses foreign investors' activities in East Germany in the context of privatization. Based on FDI theories it attempts to explore their motivations and strategies by investigating their home countries as well as their target industries. About 5 p.c. of all privatized enterprises have been acquired by foreigners. Their share in planned investment and planned employment results to be markedly larger. Foreign investors are predominantly originating from those countries which have longstanding economic relations with West Germany. The main part of foreign investment goes into manufacturing industries; into booming as well as into ailing industries. The availability of wellqualified labour appears to be of major importance for nearly all investments while contracting favourable terms of sale and taking advantage of public investment support are especially important for commitments in ailing industries. Germany's EC-membership generates further incentives such as to take advantage of the EC regulatory framework. Using East German production sites as bridgeheads to serve markets in Central Eastern Europe has been a strong motivation in the beginning but meanwhile has lost importance. Comparing foreign to West German investors, by and large their decisions seem to be driven by the same determinants.
Keywords: 330; Direktinvestition; Privatisierung; Neue Bundesländer